2016
DOI: 10.1111/scs.12391
|View full text |Cite
|
Sign up to set email alerts
|

The physical environment, activity and interaction in residential care facilities for older people: a comparative case study

Abstract: The physical environment is of particular importance for supporting activities and interactions among older people living in residential care facilities (RCFs) who spend most of their time inside the facility. More knowledge is needed regarding the complex relationships between older people and environmental aspects in long‐term care. The present study aimed to explore how the physical environment influences resident activities and interactions at two RCFs by using a mixed‐method approach. Environmental assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 55 publications
2
76
0
3
Order By: Relevance
“…Although less explicit in the accounts of our participants, uncaring conversations by staff [50] and a feeling of being forced to be co-operative with staff [8] have been indicated as hindering factors for successful transition, and it has been suggested that sensible symbols will help foster the elderly's trust in the care provided [51]. Researchers have indicated that the physical design of the LTC facility in uenced the residents' activities and interactions [52], and the design could be a hindrance or facilitator for smooth transition by way of establishing connections and relationships [53]. The design of the care facility could also enable the elderly to pursue their interests and participate in activities and to have a sense of calm and peace [38,45,52].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although less explicit in the accounts of our participants, uncaring conversations by staff [50] and a feeling of being forced to be co-operative with staff [8] have been indicated as hindering factors for successful transition, and it has been suggested that sensible symbols will help foster the elderly's trust in the care provided [51]. Researchers have indicated that the physical design of the LTC facility in uenced the residents' activities and interactions [52], and the design could be a hindrance or facilitator for smooth transition by way of establishing connections and relationships [53]. The design of the care facility could also enable the elderly to pursue their interests and participate in activities and to have a sense of calm and peace [38,45,52].…”
Section: Discussionmentioning
confidence: 94%
“…Researchers have indicated that the physical design of the LTC facility in uenced the residents' activities and interactions [52], and the design could be a hindrance or facilitator for smooth transition by way of establishing connections and relationships [53]. The design of the care facility could also enable the elderly to pursue their interests and participate in activities and to have a sense of calm and peace [38,45,52]. All our participants lived in shared rooms, but they wished for more personal space and less disturbance from their co-residents.…”
Section: Discussionmentioning
confidence: 99%
“…The participants most strongly agreed, in their ratings of their social environment and social restrictiveness, that they had freedom to do what they liked. Thus, their social housing appears to uphold at least one core value of elderly care: the protection of rights to independence and privacy [ 23 ]. Moreover, associated feelings of freedom and privacy are normative elements of the elderly’s wellbeing, and strongly indicative of the absence of strong social pressure and (thus) possibilities to “be oneself” [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when older people move to senior housing they may need support from close people or staff to get to know their new social environment, and it may be particularly important to organize social physical activities in the new environment for women, as they are more dependent than men on social networks [ 4 , 18 ]. If organisations do not support residents’ physical activity needs and preferences they tend to become inactive [ 23 ]. Support from family and staff as well as having friends who are physically active are both associated with the participation in physical activity [ 4 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…21 The residential environment itself can affect well-being. 22 However, we know little about autistic people's experiences of transferring to and living in residential care.…”
Section: Residential Care In Older Agementioning
confidence: 99%